Back to live: Returning to in-person engagement with arts and culture in the Liverpool City Region - Anisimovich, Antonina; Chapple, Melissa; Worsley, Joanne; Watkins, Megan; Billington, Josie; Balabanova, Ekaterina (Frontiers in Psychology, 2022)
On July 19th 2021, the UK government lifted the COVID-19 restrictions that had been in place since March 2020. The return to in-person events has been slow and gradual, showing that audiences are still cautious when (and if) they resume engaging in arts and culture (The Audience Agency, 2021). Patterns of audience behaviour have also changed, shifting towards local attendance, greater digital and hybrid engagement, and openness to event format changes (The Audience Agency, 2021). As the arts and cultural industry recovers from the pandemic, it is important to adopt an audience-oriented approach (Radermecker, 2021) and look at the changing patterns of engaging in arts and culture. This study aims to better understand the impact of the pandemic on the patterns of cultural and arts engagement. Eight qualitative interviews were conducted to explore the changes in arts and cultural engagement since the restrictions were lifted, focusing particularly on the audience’s experiences of returning to in-person arts and cultural events in the Liverpool City Region (LCR). Using framework analysis (Ritchie & Spencer, 1994), three themes were identified from the data: The new normal: reframing pre-pandemic and pandemic experiences of arts and culture, Re-adjusting to in-person provision, and Moving forward: online and blended provision. The findings show that the pandemic significantly altered the ways that people engage in arts and culture. As a blend of the pandemic and pre-pandemic experiences, this ‘new normal’ illustrates how the pandemic has highlighted and reconfigured the importance of arts and culture both for personal and cultural identity. Resuming in-person engagement after a long break, participants note that they were able to feel more like themselves again. Arts and culture have also proved beneficial in rebuilding resilience and confidence. After the isolating experience of the pandemic, engaging in arts and culture has also helped participants feel reconnected to others through their shared experiences. Finally, the findings suggest that online provision remains vital for many, ensuring wider inclusivity, particularly for vulnerable audiences. At the same time, it is important to acknowledge the barriers to online inclusion and the possibility of this resulting in a growing digital divide.